Regulating cell fate of human amnion epithelial cells using natural compounds: an example of enhanced neural and pigment differentiation by 3,4,5-tri-O-caffeoylquinic acid - Bejaoui, Meriem (Cell Commun Signal, 2021)
Over the past years, Human Amnion Epithelial Cells (hAECs), a placental stem cell, are gaining higher attention from the scientific community as they showed several advantages over other types of stem cells, including availability, easy accessibility, reduced rejection rate, non-tumorigenicity, and minimal legal constraint. Recently, natural compounds are used to stimulate stem cell differentiation and proliferation and to enhance their disease-treating potential. A polyphenolic compound 3,4,5-Tri-O-Caffeoylquinic Acid (TCQA) has been previously reported to induce human neural stem cell differentiation and may affect melanocyte stem cell differentiation as well. In this study, TCQA was tested on 3D cultured hAECs after seven days of treatment, and then, microarray gene expression profiling was conducted of TCQA-treated and untreated control cells on day 0 and day 7. Analyses revealed that TCQA treatment significantly enriched pigment and neural cells sets; besides, genes linked with neurogenesis, oxidation–reduction process, epidermal development, and metabolism were positively regulated. Interestingly, TCQA stimulated cell cycle arrest-related pathways and differentiation signaling. On the other hand, TCQA decreased interleukins and cytokines expression and this due to its anti-inflammatory properties as a polyphenolic compound. Results were validated to highlight the main activities of TCQA on hAECs, including differentiation, cell cycle arrest, and anti-inflammatory. This study highlights the important role of hAECs in regenerative medicine and the use of natural compounds to regulate their fate.